2021
DOI: 10.18488/journal.107.2021.91.33.43
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of External Debt: The Case of Somalia

Abstract: Most emerging countries owe substantial external debt and depend on foreign aid to achieve sustainable economic development. However, this paper's key purpose is to examine the determinants of Somalia's external debt. To achieve this, the study used the autoregressive distributed lag (ARDL) model and cointegration test to establish the short-and long-run relationships during the period from 1980 to 2018. The results show that exchange rate and domestic investment have a significant and positive effect on exter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Furthermore, a 1% increase in the trade openness ratio is accompanied by an average 0.24% increase in the external debt stock. These findings are consistent with the findings in (Mahdavi, 2004;Kızılgöl and Evren, 2014;Saheed, Sani and Idakwoji, 2015;Ogunbiyi and Okunlola, 2015;Bölükbaş, 2016;Chaudhry, Iffat and Farooq, 2017;Kocha, Iwedi and Sarakiri, 2021;Omar and Ibrahim, 2021;Çolak and Özkaya, 2021) reporting the positive effects of trade openness, fixed capital formation and general government final consumption expenditures on external debt stock. The FMOLS and CCR coefficients show that the external debt stock falls by an average of -1.17% for every 1% growth in GDP per capita.…”
Section: Variablessupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, a 1% increase in the trade openness ratio is accompanied by an average 0.24% increase in the external debt stock. These findings are consistent with the findings in (Mahdavi, 2004;Kızılgöl and Evren, 2014;Saheed, Sani and Idakwoji, 2015;Ogunbiyi and Okunlola, 2015;Bölükbaş, 2016;Chaudhry, Iffat and Farooq, 2017;Kocha, Iwedi and Sarakiri, 2021;Omar and Ibrahim, 2021;Çolak and Özkaya, 2021) reporting the positive effects of trade openness, fixed capital formation and general government final consumption expenditures on external debt stock. The FMOLS and CCR coefficients show that the external debt stock falls by an average of -1.17% for every 1% growth in GDP per capita.…”
Section: Variablessupporting
confidence: 91%
“…They examined the effects of net domestic savings, gross fiscal deficit, exchange rate, net domestic capital formation, imports, exports, terms of trade, foreign exchange reserves, debt service payments, consumer price index, interest rates, and GDP on external debt. The findings revealed that all of the variables considered in the study had a substantial impact on external debt Omar and Ibrahim (2021). investigated the factors influencing Somalia's external debt.…”
mentioning
confidence: 98%
“…The results of the study by Omar and Ibrahim [11], using the Auto Regressive Distributed Lag (ARDL) model and cointegration test, established that the exchange rate has a significant and positive effect on external debt in the long-run. One study investigating whether the exchange rate determine foreign debt in Indonesia using the ARDL approach found that, in the long-run, the foreign exchange reserves have no significant effect on foreign debt, while the exchange rate has a positive significant effect on foreign debt [10].…”
Section: Relationship Between Foreign-exchange Rate and National Debtmentioning
confidence: 99%
“…Specifically, their findings indicated that heavily indebted economies are limited in their ability to reap growth benefits from FDI, as they prioritize reducing their debt levels beyond a certain threshold. Omar and Ibrahim (2021) studied the determinants of external debt in Somalia from 1980 to 2018 using joint integration to establish short and long-term relationships and using Distributed Autoregressive Model (ARDL). They showed that the exchange rate and domestic investment had a significant and positive impact on external debt in the long run, while per capita GDP and government spending had significant and negative effects on external debt.…”
Section: Literature Reviewmentioning
confidence: 99%